Guided Multispectral Optoacoustic Tomography for 3D Imaging of the Murine Colon - Knieling, Ferdinand; Brown, Emma L.; Eckstein, Markus; Thoma, Oana-Maria; Wachter, Felix; Mandelbaum, Henriette; Ludwig, Petra; Claßen, Merle; Oraiopoulou, Mariam Eleni; Rother, Ulrich; Neurath, Markus; Wölfle, Joachim; et al. (Advanced Science, 2025)
Multispectral optoacoustic tomography is a promising medical imaging modality that combines light and sound to provide molecular imaging information at depths of several centimeters, based on the optical absorption of endogenous chromophores, such as hemoglobin. Assessment of inflammatory bowel disease has emerged as a promising clinical application of optoacoustic tomography. In this context, preclinical studies in animal models are essential to identify novel disease-specific imaging biomarkers and understand findings from emerging clinical pilot studies, however to-date, these studies have been limited by the precise identification of the bowel wall. Herein, a transrectal-absorber guide is applied, serving as a high-contrast landmark for 3D optoacoustic tomography of the colon. This study shows that guided multispectral optoacoustic tomography is able to measure changes in blood oxygenation status over the course of acute, chemically-induced colitis in mice and correlates with standard disease activity scores. This novel approach depicts intestinal hemoglobin composition non-invasively during murine inflammation. These results underscore the potential for optoacoustic imaging in translational inflammatory bowel disease research.
CRIS-Team Scopus Importer:2025-01-31
Keywords: dextran sodium sulfate induced colitis; inflammatory bowel disease; multispectral optoacoustic tomography; murine acute colitis; optoacoustic imaging; photoacoustic imaging

In Vivo Assessment of Deep Vascular Patterns in Murine Colitis Using Optoacoustic Mesoscopic Imaging - Bühler, Adrian; Brown, Emma L.; Nedoschill, Emmanuel; Eckstein, Markus; Ludwig, Petra; Wachter, Felix; Mandelbaum, Henriette; Raming, Roman; Oraiopoulou, Mariam Eleni; Paulus, Lars-Philip; Rother, Ulrich; Friedrich, Oliver; et al. (Advanced Science, 2024)
The analysis of vascular morphology and functionality enables the assessment of disease activity and therapeutic effects in various pathologies. Raster-scanning optoacoustic mesoscopy (RSOM) is an imaging modality that enables the visualization of superficial vascular networks in vivo. In murine models of colitis, deep vascular networks in the colon wall can be visualized by transrectal absorber guide raster-scanning optoacoustic mesoscopy (TAG-RSOM). In order to accelerate the implementation of this technology in translational studies of inflammatory bowel disease, an image-processing pipeline for TAG-RSOM data has been developed. Using optoacoustic data from a murine model of chemically-induced colitis, different image segmentation methods are compared for visualization and quantification of deep vascular patterns in terms of vascular network length and complexity, blood volume, and vessel diameter. The presented image-processing pipeline for TAG-RSOM enables label-free in vivo assessment of changes in the vascular network in murine colitis with broad applications for inflammatory bowel disease research.
CRIS-Team Scopus Importer:2024-11-01
Keywords: dextran sodium sulfate induced colitis; inflammatory bowel disease; murine acute colitis; optoacoustic imaging; photoacoustic imaging; raster-scanning optoacoustic mesoscopy; vessel morphology analysis

Ultrasound Localization Microscopy for the Assessment of Microvascular Circulation in Ischemic Perinatal Stroke - Regensburger, Adrian; Wachter, Felix; Denis, Louise; Mandelbaum, Henriette; Schey, Frauke; Bühler, Adrian; Siebenlist, Gregor; Schwarz, Simone; Schulz-Heise, Susanne; Rompel, Oliver; Trollmann, Regina; Wölfle, Joachim; et al. (Stroke, 2024)
CRIS-Team Scopus Importer:2024-11-15
Keywords: diagnostic imaging; microcirculation; neonate; stroke; ultrasound

Ultrasound Super-Resolution Imaging of Neonatal Cerebral Vascular Reorganization - Schwarz, Simone; Denis, Louise; Nedoschill, Emmanuel; Bühler, Adrian; Danko, Vera; Hilger, Alina; Brevis Nuñez, Francisco; Dürr, Nikola R.; Schlunz-Hendann, Martin; Brassel, Friedhelm; Felderhoff-Müser, Ursula; Reutter, Heiko Martin; et al. (Advanced Science, 2025)
During the first days of neonatal growth, the central nervous system (CNS) develops self-regulatory mechanisms to ensure constant cerebral perfusion. However, this vascular neogenesis takes place at a microscopic scale that cannot be observed with current clinical imaging techniques. Ultrasound localization microscopy (ULM) allows us to observe micro-vessels of the order of a few microns at depths of several centimeters. This can be done using conventional clinical ultrasound scanners and contrast sequences (CEUS). In this study, ULM is used to observe the human microvasculature in neonatal patients undergoing treatment for life-threatening malformations forming direct connections between the cerebral arterial and venous systems. It is observed that neuroendovascular treatment of neonatal arteriovenous malformations causes remodeling and reorganization of the cerebral vasculature by also activating corticomedullary vascular connections. ULM enables us to follow microvascular changes in human neonates with high spatio-temporal resolution. ULM may provide a novel clinical translatable tool, particularly including cerebral imaging in very young patients.
CRIS-Team Scopus Importer:2025-02-14
Keywords: CEUS; microbubbles; super-resolution imaging; ultrasound; ultrasound localization microscopy; Vein of Galen malformation